2023
DOI: 10.1212/wnl.0000000000207202
|View full text |Cite
|
Sign up to set email alerts
|

Seizure Burden and Neurologic Outcomes After Neonatal Encephalopathy

Abstract: Background and Objectives:Seizures are common during neonatal encephalopathy, but the contribution of seizure burden to outcomes remains controversial. This study aims to examine the relationship between electrographic seizure burden and neurological outcomes after neonatal encephalopathy.Methods:This prospective cohort study recruited newborns ≥36 weeks PMA around 6 hours of life between August 2014 to November 2019 from a Neonatal Intensive Care Unit. Participants underwent continuous electroencephalography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Several independent analyses have outlined that seizures/SE density over time correlates with worsening clinical prognosis in adults [49] and children [50,51]. However, association does not imply causality.…”
Section: Does Ceeg Improve Prognosis?mentioning
confidence: 99%
“…Several independent analyses have outlined that seizures/SE density over time correlates with worsening clinical prognosis in adults [49] and children [50,51]. However, association does not imply causality.…”
Section: Does Ceeg Improve Prognosis?mentioning
confidence: 99%
“… 31 A high seizure burden has previously been linked to adverse outcomes despite encephalopathy severity and antiseizure medication, highlighting the need for rapid seizure detection and treatment in the management of newborns with hypoxic-ischaemic encephalopathy. 17 , 18 , 19 , 20 The persistence of seizures during rewarming and beyond is not fully understood and is understudied. 32 , 33 , 34 The current study has shown different seizure evolution patterns in newborn infants with hypoxic-ischaemic encephalopathy that correlated with EEG background severity.…”
Section: Discussionmentioning
confidence: 99%
“… 13 , 14 , 15 , 16 Previous studies have shown a correlation between high seizure burden and death or long-term disability, or a combination of these outcomes, in infants with hypoxic-ischaemic encephalopathy, independent of the background severity and antiseizure medication. 17 , 18 , 19 , 20 The effect of seizures after the active cooling phase is not yet fully understood, but studies have suggested an association between seizures in the rewarming period and abnormal outcomes. 13 , 14 All previous published studies either analysed small numbers of infants with hypoxic-ischaemic encephalopathy or detected seizures by amplitude-integrated EEG monitoring, which is known to have limitations for the detection of all seizures in newborn infants.…”
Section: Introductionmentioning
confidence: 99%
“…However, because studies focused on associations between seizure burden and outcome, as opposed to the impact of seizure reduction on outcome, the available data could not establish whether clinical efforts to reduce seizure burden are associated with improved outcomes. Given indirect evidence, 31,70,71,73,75,90,101 experts agreed that treatment of neonatal seizures (including electrographic-only seizures) to achieve a lower seizure burden may be associated with improved outcomes. In many low-and middleincome settings, lack of access to EEG or aEEG precludes recognition of electrographic seizures or leads to misinterpretation of clinical events, potentially adding to seizure burden or overuse of ASM, with effects on outcomes for neonates in these regions.…”
Section: Consensus-based Considerationmentioning
confidence: 99%